Confecção de ferramenta web para o diagnóstico das perdas no sistema de abastecimento de água na cidade de Porto Velho - Rondônia - Costa, Prince Pereira (2018)
The municipality of Porto Velho presents one of the concessionaires with the highest rates of water supply losses, requiring a plan of action that contributes to the reduction of this index. Annually, the sanitation service provider loses, on average, R $ 124.5 million with the losses in the supply. With this, the objective was to develop a web system to strengthen the control of losses in supply with the effective participation of society and consolidating the role of social control. The research was carried out in the supply sectors of the CR1 and CR2 of the Municipality of Porto Velho, and carried out by means of bibliographical research, on-site visit to the supply units, using the Sanitation Information System (SNIS) method and the use of the WB-easycalc software to perform the calculation of losses. In the course of the study, it was verified that in the year 2017, water losses reached 19,477,641 m3 / year, with a margin of error of 6.1% (+/-), in which 18,741,792 m3 / with a real margin of error of 6.4% (+/-). It was also noted that there are independent systems with no right of use granted. To stimulate the participation of the population with online denunciations, two Website applications were developed, one by the system O.NET Framework and another by Google Sites, where the second one was created in contrapart to the first one due to its gratuitousness and irrelevance as its linkage to the site of CAERD. The use of online systems will contribute to the control of losses and, consequently, to improvements in the management of water distribution.